EFFECT OF HIGH DOSES OF ATORVASTATIN IN ACUTE MYOCARDIAL INFARCTION - SH. A. Ubaydullaev (Евразийский Кардиологический Журнал, 2019)
The aim of the study was to investigate the effect of early administration of high doses of atorvastatin in acute myocardial infarction (AMI) on the dynamics of markers of systemic inflammation.